Avaliação da eficiência energética de edificações – reflexões sobre a aplicabilidade das normas vigentes - Andréa Juliana de Oliveira Sá (2022)
This work aims to address the thermal comfort of multifamily residential buildings, to meet the demand for bioclimatic and sustainable constructions. The evaluation of thermal comfort was performed through a case study, which considered from the design phase to the construction use phase, addressing the criteria and methods established by the Brazilian standardization. The necessary data were researched for the evaluation of buildings and identified: the bioclimatic zone, the wind region, the thermal parameters to be examined and the executive procedures to meet the performance. The specific items of the standards were evaluated - NBR 15575:2013; NBR 15575:2021, NBR 15220-3:2005 and NBR15220-2:2022 – focused on thermal comfort, such as thermal transmittance and solar radiation absorbance of the external vertical sealing system (wrap) and the roofing system; using the two methods proposed by the standard, Simplified (normative) and Computational Simulation (use of EnergyPlus software - 3D modeling) - comparing them with the measurement performed in the completed building, through a Data logger (data collector). The research developed showed that the examination of the influence of the constructive characteristics of external vertical seal systems (wrap) and the coverage system combined with the position of prolonged-stay environments in critical sun exposure situations require new experiments so that the constructive methodologies adopted in the works of multifamily residential buildings, are committed to the quality of the thermal comfort of users within the building. The work allows us to conclude that it would be necessary to review the standards, so that computational simulation parameters are adopted, which really attest to the thermal comfort of the building, because the simulation makes it possible to measure the standardized procedures, but does not guarantee the attendance of all the items during the stage of use of the building.